2003
DOI: 10.1103/physrevlett.90.032301
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal Anisotropy and Correlations in the Hard Scattering Regime at RHIC

Abstract: Azimuthal anisotropy (v(2)) and two-particle angular correlations of high p(T) charged hadrons have been measured in Au+Au collisions at sqrt[s(NN)]=130 GeV for transverse momenta up to 6 GeV/c, where hard processes are expected to contribute significantly. The two-particle angular correlations exhibit elliptic flow and a structure suggestive of fragmentation of high p(T) partons. The monotonic rise of v(2)(p(T)) for p(T)<2 GeV/c is consistent with collective hydrodynamical flow calculations. At p(T)>3 GeV/c, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
216
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(238 citation statements)
references
References 29 publications
19
216
3
Order By: Relevance
“…A significant suppression of high-p T hadron production relative to a simple binary collision scaling from p + p has been observed at RHIC in central Au + Au collisions [1]. Furthermore, it was found that jetlike correlations opposite to trigger jets are suppressed and that the azimuthal anisotropy in hadron emission persists out to very high p T [2][3][4]. In contrast, no suppression effects were seen in d + Au collisions [5][6][7][8], which has led to the conclusion that the observations made in Au + Au are attributable to the high-density medium produced in such collisions and not to initial-state effects.…”
Section: Introductionmentioning
confidence: 92%
“…A significant suppression of high-p T hadron production relative to a simple binary collision scaling from p + p has been observed at RHIC in central Au + Au collisions [1]. Furthermore, it was found that jetlike correlations opposite to trigger jets are suppressed and that the azimuthal anisotropy in hadron emission persists out to very high p T [2][3][4]. In contrast, no suppression effects were seen in d + Au collisions [5][6][7][8], which has led to the conclusion that the observations made in Au + Au are attributable to the high-density medium produced in such collisions and not to initial-state effects.…”
Section: Introductionmentioning
confidence: 92%
“…On the right-hand side of Eq. [2], collision integral in terms of collision rate which change the momentum of HF quark from p to p − k is written as…”
Section: Formalismmentioning
confidence: 99%
“…At low energy, the dominant contribution to the energy loss comes from the collision processes. The inmedium energy loss of HQ is manifested in the large elliptic flow i.e., v 2 and in the suppression of high momentum heavy flavored (HF) hadrons as compared to proton-proton collision [1][2][3][4][5][6][7].Heavy quarks are produced in the initial stages of the collisions during the hard scatterings governed by perturbative quantum chromodynamics (pQCD) mostly through gluon fusion [8]; for next-to-leading order production see Ref. [9,10].…”
mentioning
confidence: 99%
“…The enhancement in v 2 in hybrid mode compared to cascade mode can be attributed to the smaller mean free path in the previous case, generating larger pressure gradients due to the assumption of mean-field approximation in the former case. Similar v 2 [52][53][54]. NCQ scaling is a natural outcome of the hadronization models based on coalescence and recombination of partons [55,56] and indicates that the collectivity developed in the early stage of the collisions is of partonic origin.…”
Section: Resultsmentioning
confidence: 89%